(untitled) (American Journal of Management, 2024)
The role of teamwork in modern organizations is more crucial than ever. This research investigates whether the COVID-19 pandemic has permanently altered Generation Z’s perceptions and behavior on team projects. A study of graduating seniors at a Southeastern university found decreased team conflicts during and after the pandemic compared to pre-pandemic levels. Task attractiveness and interpersonal cohesiveness declined during COVID-19 but rebounded post-pandemic, though not to pre-pandemic levels. These findings have implications for educational programs, workforce development, and organizational practices aimed at supporting Generation Z’s success and well-being as they transition into their careers.